Autoantibodies Against Ubiquitous and Confined Antigens in Patients With Ocular, Neuro-Ophthalmic and Congenital Cerebral Toxoplasmosis - Goldberg-Murow, Monica; Cedillo-Peláez, Carlos; Concha-del-Río, Luz Elena; Cheja-Kalb, Rashel; Salgar-Henao, María José; Orozco-Velasco, Eduardo; Luna-Pastén, Héctor; Gómez-Chávez, Fernando; Ibarra, Antonio; Correa, Dolores (Frontiers in Immunology, 2021)
Toxoplasma gondii infection can trigger autoreactivity by different mechanisms. In the case of ocular toxoplasmosis, disruption of the blood-retinal barrier may cause exposure of confined retinal antigens such as recoverin. Besides, cross-reactivity can be induced by molecular mimicry of parasite antigens like HSP70, which shares 76% identity with the human ortholog. Autoreactivity can be a determining factor of clinical manifestations in the eye and in the central nervous system. We performed a prospective observational study to determine the presence of autoantibodies against recoverin and HSP70 by indirect ELISA in the serum of 65 patients with ocular, neuro-ophthalmic and congenital cerebral toxoplasmosis. We found systemic autoantibodies against recoverin and HSP70 in 33.8% and 15.6% of individuals, respectively. The presence of autoantibodies in cases of OT may be related to the severity of clinical manifestations, while in cases with CNS involvement they may have a protective role. Unexpectedly, anti-recoverin antibodies were found in patients with cerebral involvement, without ocular toxoplasmosis; therefore, we analyzed and proved cross-reactivity between recoverin and a brain antigen, hippocalcin, so the immunological phenomenon occurring in one immune-privileged organ (e.g. the central nervous system) could affect the environment of another (egg. the eye).